2017
DOI: 10.1097/shk.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Intestinal Damage and their Relation to Cytokine Levels in Cardiac Surgery Patients

Abstract: Longer duration of ECC is associated with a more pronounced release of intestinal injury markers and inflammatory cytokines, but intestinal injury markers are not directly related to the observed increase in cytokine levels or GI-symptoms. These findings indicate that ECC duration contributes to the cytokine response observed in cardiac surgery patients and that intestinal injury itself is not a causative factor for this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…In comparison, a small positive correlation was reported between I‐FABP and CLDN‐3. This finding is supportive of previous evidence showing urinary I‐FABP and CLDN‐3 to weakly correlate ( r = 0.38) in patients with major nonabdominal surgery (Habes et al, ). The expression of CLDN‐3 across multiple tissues might partially explain why this correlation was not stronger (Thuijls, Derikx, Haan, et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In comparison, a small positive correlation was reported between I‐FABP and CLDN‐3. This finding is supportive of previous evidence showing urinary I‐FABP and CLDN‐3 to weakly correlate ( r = 0.38) in patients with major nonabdominal surgery (Habes et al, ). The expression of CLDN‐3 across multiple tissues might partially explain why this correlation was not stronger (Thuijls, Derikx, Haan, et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…This finding compares well to the only previous exercise study, where concentrations increased directly following a 1 hr moderate-intensity (70% VO 2max ) run in both temperate (22°C; 6.7 > 7.6 ng ml −1 ) and hot (33°C; 6.6 > 8.2 ng ml −1 ) ambient environments (Yeh et al, 2013). The clinical relevance of this small, transient increase in CLDN-3 following exercise is poorly understood, though it is modest in comparison with the magnitude of increase (4-20-fold) shown acutely following major nonabdominal surgery (Habes et al, 2017;Typpo et al, 2015). Promisingly, of all the GI barrier integrity biomarkers compared, CLDN-3 displayed the strongest relative and absolute reliability.…”
Section: F I G U R E 4 Gi Mt Responses To Ehstmentioning
confidence: 99%
“…As many risk factors exist, such as primary cardiac diseases, the use of vasopressors, ischemia-reperfusion injury during CPB, and surgical stress, postoperative cardiac surgery patients usually patients manifested as abnormal appetite, nausea and vomiting, abdominal distension, bowel sound attenuation, which means gastrointestinal dysfunction. [ 6 , 7 ] Also gastrointestinal dysfunction nowadays is considered to be a major risk factor for MODS and gut derived infection in patients with critical illness, and is related to poor prognosis. [ 9 ] As is well known, the gastrointestinal function is very complicated, and many researchers tried to establish different evaluating systems to assess it in ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, after operation, gastrointestinal injury, even gastrointestinal dysfunction often appears. [ 6 , 7 ] As is well known, gut is a center organ of surgical stress, and gastrointestinal dysfunction plays a pivotal role in the progression of infective complications and multiple organ dysfunction syndrome (MODS) after operation, which would lead to a poor outcome in postoperative cardiac surgery patients. [ 8 , 9 ] Early identification of postoperative cardiac surgery patients at risk of developing infective complications and MODS is important for the optimization of early aggressive management, which will reduce the length of ICU stay and improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, no studies specifically evaluated TJ proteins enriched in pulmonary or renal epithelium. Seven studies investigated GI-derived TJ markers, in the settings of severe malnutrition [ 36 ], non-GI surgery [ 37 ], congenital heart surgery requiring cardiopulmonary bypass [ 38 , 39 ], and general critical illness [ 40 – 42 ]. All together, these studies found disrupted TJs as assessed by histology or electron microscopy.…”
Section: Resultsmentioning
confidence: 99%